Addressing student sexual violence in higher education : a good practice guide - Humphreys, Clarissa J.; Towl, Graham J. (Emerald Publishing Limited, 2020)
Sexual violence is a well-documented issue within Higher Education and wider society. Students subjected to sexual violence suffer impacts to their physical, psychological, emotional, behavioural, and practical wellbeing, which have significant effects on their studies. Higher Education Institutions have a duty to ensure students can access their education in environments that are safe, without fear, harassment, or violence. Currently, there is a critical lack of guidance on how to meaningfully address this issue in practical terms. Advice offered to the sector, particularly in the UK, has focused on why Higher Education Institutions need to address sexual violence, offering general principles to shape institutions' responses. This unique text is the first to offer practical guidance on how to address sexual violence, utilising a comprehensive institution-wide approach. This ethical method is trauma-informed and survivor-centred whilst being intersectional and requiring perpetrator accountability. The authors provide how-to level information on staffing, policy writing, responding to disclosures, developing comprehensive prevention and response education programmes, conducting trauma-informed investigations, adjudication and sanctioning processes and considering sanctioning guidelines for sexual violence. This is a ground-breaking resource for practitioners, senior leaders, policy makers, student services administrators, educators, investigators and adjudicators in Higher Education.
Includes index.
Keywords: Campus violence -- Prevention.; College students -- Crimes against -- Prevention.; Sex crimes -- Prevention.; Social Science, Sexual Abuse & Harassment.; Causes & prevention of crime.; elektronické knihy; electronic books